Electrical performance of curcuma longa extract dye using SnO2- based photoanode dye-sensitized solar cell - Norizan, Mohd Natashah; Mohamad, Ili Salwani; Idris, Siti Norhafizah; Magiswaran, Kaiswariah; Mahmed, Norsuria; Abal Abas, Zuraida (Penerbit Universiti Malaysia Perlis (UniMAP), 2022)
Due to their low output costs, straightforward manufacturing, and high effectiveness, dye-sensitized solar cell (DSSC) has a large following interest in the solar energy industry. Furthermore, due to its outstanding properties, tin oxide (SnO2) is an appealing semiconducting material suitable as a photoanode in DSSCs. In this research, the photoelectrodes of DSSC were fabricated using commercial SnO2 nanoparticles and sensitized with inorganic and organic dyes, N719 and Curcuma longa (turmeric) extract dye. On top of that, a platinum (Pt) counter electrode, iodide electrolyte and fluorine-doped tin oxide (FTO) coated glass substrate were used to fabricate the DSSC. The crystallographic structure and surface morphology of the SnO2 nanopowder were identified using X-ray diffraction (XRD) and scanning electron microscopy (SEM) characterizations respectively. In addition, UV-Visible and current density-voltage curves were used to analyze the optical properties of the photoanodes and the cell’s electrical performance. As a result, it was found that the DSSC fabricated with N719 dye exhibited higher efficiency in contrast with the turmeric extract dye with SnO2 photoanodes.